MANAJEMEN APLIKASI SISTEM ZONASI DALAM PENERIMAAN PESERTA DIDIK BARU (PPDB) TINGKAT SEKOLAH MENENGAH PERTAMA (SMP) - Mukhfid, Mufid (Universitas Wiralodra, 2020)
In order to carry out the mandate of the Ministry of Education and Culture (Kemendikbud). And in 2019 the Ministry of Education and Culture implemented a system called the Zoning System which regulates student admission in a zone that will be applied to all regions in Indonesia which are set according to Minister of Education and Culture Regulation No. 51 of 2018[1]. Currently in the New Student Admissions Process (PPDB) in its application is still manual and uses an offline system that is divided in every school so that its implementation is still experiencing problems, where it is difficult to get valid location data for distance determination, lack of transparency of information, less effective, even many schools do not follow the rules in accordance with existing regulations. Methodology in the Development of